SOCIAL ENTREPRENEURSHIP IN TURKEY: SOCIAL SOLUTION FOR REFUGEE PROBLEM - Mollaoğulları, Batuhan Fatih; Temel, Ramazan (International Journal of Contemporary Economics and Administrative Sciences, 2018)
The definition of social entrepreneurship includes systematic activities aimed at solving many social problems, from human rights, environment, development, social exclusion, poverty reduction. Social entrepreneurship makes an unlimited effort by focusing on social change, ignoring institutional and organizational norms and boundaries. In this sense, generally in the world; In particular, the refugee problem in Turkey has made the concept of social entrepreneurship even more important. In this study, the concept of social entrepreneurship will be discussed and the contribution of social entrepreneurship to solve the refugee problem in Turkey will be discussed.